PENINGKATAN HASIL BELAJAR SISWA KELAS IVB PEMBELAJARAN IPAS MELALUI MEDIA PUZZLE DI SDN PETERONGAN - Isbat Dzikril Anam; Ngurah Ayu Nyoman; Fine Reffiane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is useful to improve the learning outcomes of students in class IVB learning ipas through puzzle media at SDN Peterongan. The research used a Classroom Action Research (PTK) design and was conducted over two cycles. This assessment shows that there is an increase in learning outcomes in each cycle. In the pre-cycle, the students who were complete were 8 students or the percentage of complete 33% while those who were not complete were 16 students or the percentage of incomplete 67%. In cycle I, the students who were complete were 16 students or a percentage of 67% while the students who were not complete were 8 students or a percentage of 33% incomplete. In cycle II, the students who were complete were 20 students or a percentage of 83% complete while the students who were not complete were 4 students or a percentage of 17% incomplete. It can be concluded that there is an increase in the learning outcomes of class IVB students learning ipas by using puzzle media.